Investment preferences of institutional investors in Indonesia: A comparative analysis of pressure-sensitive and pressure-insensitive groups - Dwi Prastowo Darminto; Abdulloh Mubarok; Nurmala Ahmar (Investment Management & Financial Innovations)
This study investigates the investment preferences of institutional investors in Indonesia, focusing on the factors influencing stock selection. A comparative analysis is conducted between pressure-sensitive and pressure-insensitive investor groups to explore how different factors such as corporate social responsibility, corporate governance, shariah-compliant stocks, and financial indicators, including profitability, liquidity, and risk, affect their investment decisions. Data from 938 observations across 253 manufacturing companies listed on the Indonesia Stock Exchange were analyzed using panel data regression. The period was chosen because it captures a stable economic period in Indonesia, allowing for an accurate assessment of investment patterns without major external shocks. The results reveal that institutional investors favor stocks listed on the Indonesia Shariah Stock Index (ISSI), perceived as low-risk investments. Pressure-sensitive investors, such as banks and insurance companies, prefer companies with close business affiliations, while pressure-insensitive investors, such as mutual funds and pension funds, prioritize financial performance and corporate governance. Additionally, the study finds that the debt-to-asset ratio and inclusion in the Shariah index significantly affect institutional ownership, indicating a preference for leveraged companies with ethical investment profiles. This study provides a deeper understanding of the varying preferences between institutional investor groups, highlighting the significance of ethical considerations, financial stability, and corporate governance in emerging markets.